Effects of geometrical parameters on the flow and heat transfer characteristics in trapezoidal-corrugated channel using nanofluid - Ahmed M.A.; Yusoff M.Z.; Shuaib N.H. (2023)
In this article, laminar forced convection heat transfer of copper-water nanofluid in trapezoidal-corrugated channel has been numerically investigated. The two-dimensional governing continuity, momentum and energy equations in body-fitted coordinates are discretized using finite volume approach and solved iteratively using SIMPLE technique. In this study, the Reynolds number and nanoparticle volume fractions are in the ranges of 100-700 and 0-5%, respectively. The effect of geometrical parameters such as the amplitude and wavelength of the corrugated channel, nanoparticle volume fraction and Reynolds number on the velocity vectors, temperature contours, pressure drop and average Nusselt number have been presented and analyzed. The results show that the average Nusselt number enhances with increase in nanoparticles volume fraction and with the amplitude of corrugated channel but this enhancement accompanied by increases in pressure drop. In addition, as the wavelength of corrugated channel decreases, the average Nusselt number increases and the pressure drop decreases. 2012 Elsevier Ltd.